The Effect of Digital Marketing and Brand Image on Customer Trust and Its Implication for Customer Loyalty in the E-Commerce Industry - Sri Rezeki; Petrus Loo; Desma Erica Maryati Manik; Elisabeth Nainggolan; Herni Suryani (Dinasti International Journal of Education Management and Social Science, 2026)
The rapid growth of e-commerce has intensified competition among digital businesses, making customer trust and loyalty critical determinants of long-term sustainability. In this context, digital marketing activities and brand image play an increasingly important role in shaping customers’ perceptions and behavioral intentions. This study aims to examine the effect of digital marketing and brand image on customer trust and its implications for customer loyalty in the e-commerce industry. This research employs a quantitative approach using a survey method. Data were collected from e-commerce customers who have prior experience in online transactions. The data were analyzed using Structural Equation Modeling (SEM) to test the proposed relationships and the mediating role of customer trust. Digital marketing is measured through indicators such as online content quality, interactivity, and personalization, while brand image reflects customers’ overall perceptions and associations with the brand. The results indicate that digital marketing has a positive and significant effect on customer trust. Brand image is also found to significantly influence customer trust. Furthermore, customer trust has a positive and significant effect on customer loyalty. The findings further reveal that customer trust mediates the relationship between digital marketing and customer loyalty, as well as between brand image and customer loyalty. These results suggest that customer trust serves as a key mechanism through which digital marketing efforts and brand image translate into loyal customer behavior. This study contributes to the marketing literature by providing empirical evidence on the role of customer trust in the e-commerce context. From a managerial perspective, the findings imply that e-commerce firms should focus on developing effective digital marketing strategies and maintaining a strong brand image to foster customer trust and enhance customer loyalty in a highly competitive digital marketplace.